Whole-sporozoite malaria vaccines: where we are, where we are going - Diana Moita; Miguel Prudêncio (EMBO Molecular Medicine)
Abstract The malaria vaccination landscape has seen significant advancements with the recent endorsement of RTS,S/AS01 and R21/Matrix-M vaccines, which target the pre-erythrocytic stages of Plasmodium falciparum (Pf) infection. However, several challenges remain to be addressed, including the incomplete protection afforded by these vaccines, their dependence on a single Pf antigen, and the fact that they were not designed to protect against P. vivax (Pv) malaria. Injectable formulations of whole-sporozoite (WSpz) malaria vaccines offer a promising alternative to existing subunit vaccines, with recent developments including genetically engineered parasites and optimized administration regimens. Clinical evaluations demonstrate varying efficacy, influenced by factors, such as immune status, prior exposure to malaria, and age. Despite significant progress, a few hurdles persist in vaccine production, deployment, and efficacy in malaria-endemic regions, particularly in children. Concurrently, transgenic parasites expressing Pv antigens emerge as potential solutions for PvWSpz vaccine development. Ongoing clinical studies and advancements in vaccine technology, including the recently described PfSPZ-LARC2 candidate, signify a hopeful future for WSpz malaria vaccines, which hold great promise in the global fight against malaria.